2023
DOI: 10.1001/jamanetworkopen.2023.9196
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factors and Clinical Importance of Enlarged Perivascular Spaces by Whole-Brain Investigation in the Multi-Ethnic Study of Atherosclerosis

Abstract: ImportanceEnlarged perivascular spaces (ePVSs) have been associated with cerebral small-vessel disease (cSVD). Although their etiology may differ based on brain location, study of ePVSs has been limited to specific brain regions; therefore, their risk factors and significance remain uncertain.ObjectiveToperform a whole-brain investigation of ePVSs in a large community-based cohort.Design, Setting, and ParticipantsThis cross-sectional study analyzed data from the Atrial Fibrillation substudy of the population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A study on chronic traumatic brain injury did not find PVS burden being associated with brain age (Hicks et al, 2023). Studies that analysed the PVS association with age in different regions had conflicting results, with the majority reporting a positive association/correlation with age in all regions, and one study finding a negative association between age and PVS volume in the temporal region (Charisis et al, 2023; N=1026).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study on chronic traumatic brain injury did not find PVS burden being associated with brain age (Hicks et al, 2023). Studies that analysed the PVS association with age in different regions had conflicting results, with the majority reporting a positive association/correlation with age in all regions, and one study finding a negative association between age and PVS volume in the temporal region (Charisis et al, 2023; N=1026).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven out of thirteen studies identified a positive association between hypertension and PVS burden (Ballerini et al, 2019; Huang, Zhu, et al, 2021b; Wang et al, 2021; Wang, Chappell, et al, 2016; Cheng et al, 2022; Hadad et al, 2022; Charisis et al, 2023; Evans et al, 2023; Tachibana et al, 2024; Zebarth et al, 2023; Duperron et al, 2023). Duperron et al, (2023), the largest study amongst the ones included, found causal associations of high blood pressure with BG and hippocampal PVS, and of BG PVS and hippocampal PVS with stroke, accounting for blood pressure, even after Mendelian randomisation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When neuroinflammation is discussed, the CNS resident immune microglia cell(s) (MGC) most often comes to mind and is discussed extensively in the literature [52][53][54][55][56]; however, in this narrative review the focus has been primarily on the rPVMΦ that reside within the PVS by TEM studies. This is not only because PVS and EPVS are important [2,8,57] but also because both MGCs and PVMΦs have been rapidly gaining interest over the past decade. For example, PubMed (NIH National Library of Medicine) reference entries regarding MGCs have increased from 68/year in 2008 to 374/year in 2022 an increase 306/year.…”
Section: Reactive Juxtavascular Microglia Cells (Rjvmgcs) Neuroinflam...mentioning
confidence: 99%